CHARACTER-BASED ECONOMIC LEARNING IMPLEMENTATION AND TEACHER’S REINFORCEMENT ON STUDENT’S AFFECTIVE COMPETENCE IN MINIMIZING HOAX - Hendro Prasetyono; Agus Abdillah; Toto Widiarto; Heru Sriyono (LPMPP Universitas Negeri Yogyakarta, 2018)
Abstract: Minimizing hoaxes that occur in students is closely related to learning outcomes in the affective domain. Therefore, the purpose of this research is to find out and analyze implementation of character- based economic learning and teacher’s reinforcement influence on student’s affective competence. Type of this research is descriptive and associative analysis. The populations of this research were 10 th class of senior high school student in East Jakarta amounting to 1793 students. The sample in this research amounted to 95 students. The sampling method was done by using proportionate random sampling. Data collection is done by filling questionnaires. Analysis of the data used is descriptive statistic and multiple regression. The results showed that there were simultaneously positive and significant effects between implementation of character-based economic learning and teacher’s reinforcement on students’ affective competencies in minimizing hoax news on online social media. However, partially teacher’s reinforcement has a positive but not significant effect on students’ affective competencies. Overall, the magnitude of the effect is known to be 43.50%. This gives a considerable meaning, because almost half of its contribution. Even though there are still many other factors that contribute to affective competence, namely the remaining 56.50% as other factors not examined in this study Keywords: affective competence, hoax information, implementation of character-based economic learning, reinforcement IMPLEMENTASI PEMBELAJARAN EKONOMI BERBASIS KARAKTER DAN REINFORCEMENT GURU PENGARUHNYA TERHADAP KOMPETENSI AFEKTIF SISWA DALAM MEMINIMALISIR HOAX Abstrak: Meminimalisir hoax yang terjadi pada siswa, erat kaitannya dengan hasil belajar pada ranah afektif. Oleh karena itu, tujuan penelitian ini adalah untuk mengetahui dan menganalisis pengaruh implementasi pembelajaran ekonomi berbasis karakter dan reinforcement guru terhadap kompetensi afektif siswa. Penelitian ini menggunakan analisis deskriptif dan asosiatif. Populasi penelitian adalah siswa kelas X ilmu sosial di Jakarta Timur yang berjumlah 1.793 siswa dan sampel penelitian sebanyak 95 siswa. Teknik pengambilan sampel dilakukan dengan menggunakan proporsional random sampling. Pengumpulan data dilakukan dengan kuesioner. Analisis data yang digunakan adalah deskriptif dan regresi berganda. Hasil penelitian menunjukkan bahwa secara simultan terdapat pengaruh positif dan signifikan implementasi pembelajaran ekonomi berbasis karakter dan reinforcement guru terhadap kompetensi afektif siswa dalam meminimalkan berita hoax di media sosial onlin e. Namun, reinforcement guru memiliki pengaruh positif tetapi tidak signifikan terhadap kompetensi afektif siswa. Secara keseluruhan, besarnya pengaruh diketahui 43,50%. Hal ini memberi makna cukup besar, sebab mencakup hampir separuh kontribusinya. Padahal masih banyak faktor lain yang berkontribusi terhadap kompetensi afektif yaitu 56,50% sisanya sebagai faktor lain yang tidak diteliti dalam penelitian ini. Kata kunci: kompetensi afektif, berita hoax, implementasi pembelajaran ekonomi berbasis karakter, reinforcemen